2012
DOI: 10.1302/0301-620x.94b7.28603
|View full text |Cite
|
Sign up to set email alerts
|

The long-term post-operative electromyographic evaluation of patients who have undergone carpal tunnel decompression

Abstract: We present the electromyographic (EMG) results ten years after open decompression of the median nerve at the wrist and compare them with the clinical and functional outcomes as judged by Levine's Questionnaire. This retrospective study evaluated 115 patients who had undergone carpal tunnel decompression at a mean of 10.47 years (9.24 to 11.36) previously. A positive EMG diagnosis was found in 77 patients (67%), including those who were asymptomatic at ten years.It is necessary to include both clinical and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Results were normal in 24; mild or moderate involvement of the median nerve in the carpal canal was present in 19 (this includes six of seven with previous carpal tunnel release that had triggered the complex regional pain syndrome, considered by the neurophysiologist as being normal changes after surgery). 21 In only two of 45 was the compression of the median nerve graded as moderate-severe or severe.…”
Section: Methodsmentioning
confidence: 99%
“…Results were normal in 24; mild or moderate involvement of the median nerve in the carpal canal was present in 19 (this includes six of seven with previous carpal tunnel release that had triggered the complex regional pain syndrome, considered by the neurophysiologist as being normal changes after surgery). 21 In only two of 45 was the compression of the median nerve graded as moderate-severe or severe.…”
Section: Methodsmentioning
confidence: 99%
“…Electromyography (EMG), nerve conduction velocity (NCV) studies or ultrasound is of limited use after a CTR. Prior research showed that EMG/NCV findings and the cross-sectional area (CSA) of the nerve can still be abnormal months to years following CTR in asymptomatic patients (Faour-Martín et al., 2012). However, if EMG/NCV studies or ultrasound is used to diagnose CTS preoperatively, improvement of EMG/NCV findings and a decrease in the CSA after CTR may suggest a successful release (Ise et al., 2021; Kanatani et al., 2014; Oh et al., 2017; Smidt and Visser, 2008; Vögelin et al., 2010).…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Assessing nerve function for persistent symptoms after surgery is a reasonable approach, yet interpreting postoperative results remains challenging because the extent of improvement in nerve function after CTR varies widely (Bergquist and Hammert, 2013; El-Hajj et al., 2020; Sonoo et al., 2018). In addition, comparing pre- and postoperative NCS may not definitively determine whether symptoms stem from residual median nerve compression (Faour-Martín et al., 2012). Only significant worsening of neurophysiology may suggest inadequate decompression or iatrogenic damage.…”
Section: Revision Median Nerve Decompressionmentioning
confidence: 99%